Peran Guru dalam Menghadapi Tantangan Munculnya Teknologi Digital Khususnya Smartphone - Walda Astria; Delsri Alik Matota; Frisilya Priska; Aryanto Dwi saputra; Ronaldo Stefanus (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
The emergence of smartphone technology has brought significant changes to the world of education while simultaneously creating new challenges for teachers. This study aims to identify and analyze the challenges teachers face in the learning process following the widespread use of smartphones by students. The method used was a literature review, examining various sources on digital learning, student behavior, and the impact of technology on the educational process. The results indicate that teachers face various challenges, including student concentration disruptions due to entertainment content, over-reliance on technology, student access to age-inappropriate content, lack of parental supervision, unequal access to devices, and the emergence of digital ethics issues such as social media misuse and cyberbullying. These conditions require teachers to have stronger digital competencies, adaptive classroom management skills, and pedagogical strategies that balance technology use with character building and healthy digital discipline. To address these challenges, four main strategies can be implemented: enhancing digital competence, integrating character values in technology use, innovating learning methods, and building collaboration among teachers in designing digital learning.